Working in writing - Burling, Alexis (Career files., 2018)
Explores a range of jobs utilizing writers, surveying what people do in each job, where they work, the tools they use, and each job's average salary. Includes color photographs, sidebars, statistics, reflection questions, a glossary, and further resources.